Work Motivation Strategies In An Effort To Increase Work Achievement : Study At PT. Kalimantan Mandiri Success - Junaidi Junaidi; Gusti Meinar Girda Ariani; Periyadi Periyadi (International Journal of Economics and Management Sciences, 2024)
Kalimantan Mandiri Sukses is a service company engaged in the distribution of mining products, especially coal and heavy mining equipment transportation services which has been operating for more than ten years in Banjarmasin. This research aims to analyze work motivation strategies in an effort to improve work performance. Apart from that, another aim is to provide insight into the factors that influence employee work motivation and provide recommendations for increasing employee work motivation and improving their work performance. The method used in this research is descriptive qualitative with data collection techniques through interviews and observation. The data were analyzed using content analysis techniques, with the respondents in this study being employees of PT. Kalimantan Mandiri Sukses was selected using purposive sampling. The research results show that there are several work motivation factors that influence employee work performance, such as incentives, recognition, social support, work environment, and career development. Incentives provided by companies in the form of salaries and bonuses are the main factors in motivating employees. Apart from that, recognition and appreciation from management, social support from colleagues and the work environment, as well as clear career development are also factors that are no less important in motivating employees to improve their work performance at PT. Kalimantan Independent Success.